Bioaccumulation and Health Risk Assessment of Lead and Cadmium in Some Organs of Fish Siganus Rivulatus from Lake Timsah and Bitter Lakes, Suez Canal, Egypt - Amaal Omar Balq; Khalid Mohamed El-Moselhy (African Journal of Advanced Pure and Applied Sciences, 2023)
Seawater pollution is the serious environmental problems and possess a major threat to the human health and global ecosystems. This study aimed to estimate the concentration of Pb and Cd in the muscles, liver and gills of fish Siganus rivulatus caught by commercial fisheries from Lake Timsah and Bitter Lakes (Suez Canal) during winter and summer 2020. Fish muscles recorded the lowest concentration of Pb and Cd among the studied organs with the values of 0.216 - 0.424 and 0.091-0.112 µg/g, respectively. While gills accumulated the highest concentrations of the investigated two metals. Moreover, Pb showed concentrations in the fish organs higher than Cd. Finally, by comparing the present concentrations of metals in fish muscles with the maximum permissible limit (MPL) recommended by the international organizations, in addition to calculate the estimated daily intake (EDI); it can be concluded that muscles of the present fish are safe for human consumption.